Yishen Qingli Heluo Granule in the Treatment of Chronic Kidney Disease: Network Pharmacology Analysis and Experimental Validation - Sun X; Huang Y; Zhu S; Yan J; Gan K; Xu Z; Wang S; Kang X; Zhang J; Sun W (Dove Medical Press, 2022)
Xian Sun,1 Yiting Huang,1 Sha Zhu,1 Jin Yan,2 Ke Gan,3 Zijing Xu,4 Shuaishuai Wang,4 Xiaoyu Kang,4 Junfeng Zhang,4 Wei Sun2 1The First Clinical Medical College, Nanjing University of Chinese Medicine, Nanjing, 210023, People’s Republic of China; 2Department of Nephrology, Jiangsu Province Hospital of Chinese Medicine, Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, 210029, People’s Republic of China; 3Department of Rheumatology, Jiangsu Province Hospital of Chinese Medicine, Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, 210029, People’s Republic of China; 4School of Medicine & Holistic Integrative Medicine, Nanjing University of Chinese Medicine, Nanjing, 210023, People’s Republic of ChinaCorrespondence: Wei Sun, Department of Nephrology, Jiangsu Province Hospital of Chinese Medicine, Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, 210029, People’s Republic of China, Tel +86-13505199810, Email yfy0074@njucm.edu.cn Junfeng Zhang, School of Medicine & Holistic Integrative Medicine, Nanjing University of Chinese Medicine, Nanjing, 210023, People’s Republic of China, Tel +86-13805186836, Email Zhangjunfeng419@njucm.edu.cnBackground: Chronic kidney disease (CKD) is considered a global public health problem with high morbidity and mortality. Yishen Qingli Heluo granule (YQHG) is representative traditional Chinese medicine (TCM) remedy for clinical treatment of CKD. This study aims to explore the mechanism of YQHG on CKD through network pharmacology and experimental validation.Methods: Traditional Chinese Medicine Systems Pharmacology (TCMSP) database and wide-scale literature mining were applied to screen active compounds of YQHG. Multiple bioinformatic tools and online databases were applied by us to obtain relevant targets of YQHG and CKD. The intersection targets between YQHG and CKD were considered as candidate targets. The compound-target, herb-candidate target and protein–protein interaction networks were constructed and visualized for topological analyses. GO and KEGG enrichment analyses were conducted to determine the biological processes and signaling pathways. Molecular docking was used to verify the reliability of network pharmacology. Finally, pharmacological evaluation was performed to explore the mechanism of YQHG against CKD on a 5/6 nephrectomy model.Results: Seventy-nine candidate targets, ten core biological processes and one key signaling pathway (p53) were screened. PTGS2 was identified as a key target based on H-CT network. The molecular docking showed that Quercetin, Kaempferol, Luteolin were three key compounds with the best binding activity. In addition, IL6 and Quercetin could form a stable complex with high binding affinity (− 7.29 kcal/mol). In vivo experiment revealed that YQHG improved kidney function and fibrosis in 5/6 nephrectomized rats. Moreover, the decreased expression of PTGS2, IL6, and the increased expression of p53 were observed in kidney tissue. Notably, the gut microbiota of rats treated with YQHG was reshaped, which was characterized by a reduced ratio of Firmicutes/Bacteroidota.Conclusion: Our results predicted and verified the potential targets of YQHG on CKD from a holistic perspective, and provided valuable direction for the further research of YQHG.Keywords: Yishen Qingli Heluo granule, network pharmacology, chronic kidney disease, 5/6 nephrectomy, gut microbiota